2018
DOI: 10.3390/hydrology5030047
|View full text |Cite
|
Sign up to set email alerts
|

Anticipate Manning’s Coefficient in Meandering Compound Channels

Abstract: Estimating Manning's roughness coefficient (n) is one of the essential factors in predicting the discharge in a stream. Present research work is focused on prediction of Manning's n in meandering compound channels by using the Group Method of Data Handling Neural Network (GMDH-NN) approach. The width ratio (α), relative depth (β), sinuosity (s), Channel bed slope (S o ), and meander belt width ratio (ω) are specified as input parameters for the development of the model. The performance of GMDH-NN is evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 50 publications
0
15
0
3
Order By: Relevance
“…Studies have demonstrated a wide range of forecasting accuracies using AI models with the geographic topographies of the test sites despite their success in other fields [15][16][17][18]. e development of a model that will be used to forecast in any environmental condition is an aspect yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated a wide range of forecasting accuracies using AI models with the geographic topographies of the test sites despite their success in other fields [15][16][17][18]. e development of a model that will be used to forecast in any environmental condition is an aspect yet to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…There is no clear criterion to divide the entire data into training and testing data. However, the length of the training data is typically set at 70-90% of the total data length [27,28]. Thus, in this study, the scaled data were then partitioned into training (2008-2014, data length = 2557 (70%)) and testing datasets (2015-2017, data length = 1096 (30%)).…”
Section: Data Usedmentioning
confidence: 99%
“…Error analysis is also performed by obtaining mean percentage error (ME), standard deviation (SD), coe cient of determination (R 2 ), mean absolute error (MAE), root mean square error (RMSE), and mean absolute percentage error (MAPE) [26,27]. e percentage of mean error for prediction of C p by various models and their standard deviation is shown in Figure 11.…”
Section: Error Analysismentioning
confidence: 99%